M + s = 10 or s = 10 - m
<span>3m + 2s = 23 </span>
<span>substitute first equation into second equation: </span>
<span>3m + 2(10 - m) = 23 </span>
<span>3m + 20 - 2m = 23 </span>
<span>m = 3 </span>
<span>using first equation: </span>
<span>s = 10 - 3 = 7 </span>
<span>check using second equation: </span>
<span>3(3) + 2(7) = 23 </span>
<span>9 + 14 = 23 checks </span>
<span>He hit 7 stationary and 3 moving targets.</span>
-- 100% of the original number is ALL of it.
-- If it's increased by that amount, it becomes DOUBLE
(twice as much as) what it was originally.